Control and protect: collaboration, carceral protection, and domestic sex trafficking in the United States - Musto, Jennifer (University of California Press, 2016)
"Control and Protect explores the meaning and significance of efforts designed to combat sex trafficking in the United States. A striking case study of the new ways in which law enforcement agents, social service providers, and nongovernmental advocates have joined forces in this campaign, this study reveals how these collaborations consolidate state power and carceral control. This book examines how partnerships forged in the name of fighting domestic sex trafficking have blurred the boundaries between punishment and protection, victim and offender, and state and nonstate authority"--Provided by publisher